IMPLEMENTATION OF PROFESSIONAL ZAKAT OF STATE CIVIL APPARATUS IN INDONESIAN IN ISLAMIC LAW PERSPECTIVE - Amrin; Ade Irmah Imamah; Nurrahmania; Adi Priyono (Universitas Muhammadiyah Surakarta, 2023)
The main problem of this research is the Implementation of Professional Zakat for State Civil Apparatus in the Perspective of Islamic Law Study in the Government of Ambalawi District, Bima Regency West Nusa Tenggara Province. So that the research objectives are 1) How is the Income of State Civil Apparatus in the Ambalawi District Government; 2) Barriers to the State Civil Apparatus in the Ambalawi District Government; 3) Review of Islamic Law on the Practice of Professional Zakat among State Civil Apparatus of the Ambalawi District Government. This type of research is classified as descriptive qualitative in the form of field research with the research approach used being an empirical approach and Islamic jurisprudence. The data sources of this research are primary data and secondary data. Data collection methods used are observation, interviews, and documentation, while the data processing and analysis technique is carried out through three stages, namely: data reduction, data presentation, and concluding. Based on the results of research in the field, it can be stated that the implementation of the Professional Zakat for State Civil Apparatus Government of Ambalawi District, Bima Regency has not been fully implemented. Because the income they receive has not reached the nishab limit by the ijtihad agreement of the scholars and the MUI Fatwa number 3 of 20013 regarding zakat income with a nishab of 85 grams of gold. Employees also have obstacles because of the lack of socialization about professional zakat and the lack of trust in Baznas and amil zakat institutions. In the view of Islamic law, a person is only obliged to pay zakat if his assets reach the nishab.